2012
DOI: 10.1007/s00127-011-0470-9
|View full text |Cite
|
Sign up to set email alerts
|

Childhood problem behavior and parental divorce: evidence for gene–environment interaction

Abstract: ObjectiveThe importance of genetic and environmental influences on children’s behavioral and emotional problems may vary as a function of environmental exposure. We previously reported that 12-year-olds with divorced parents showed more internalizing and externalizing problems than children with married parents, and that externalizing problems in girls precede and predict later parental divorce. The aim of the current study was to investigate as to whether genetic and environmental influences on internalizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 36 publications
0
12
0
3
Order By: Relevance
“…Children whose parents are going through a divorce engage in anxious behaviors and can typically experience denial, abandonment, preoccupation, anger and hostility, immaturity or hyper maturity, blaming, and acting out (138). If these emotions persist, children can sometimes develop mental disturbances (138).…”
Section: Divorcementioning
confidence: 99%
“…Children whose parents are going through a divorce engage in anxious behaviors and can typically experience denial, abandonment, preoccupation, anger and hostility, immaturity or hyper maturity, blaming, and acting out (138). If these emotions persist, children can sometimes develop mental disturbances (138).…”
Section: Divorcementioning
confidence: 99%
“…For parent ratings of conduct problems, the Child Behavior Checklist [CBCL; Achenbach and Rescorla, 2001] is often employed. Scores are taken from the DSM-Oriented Scale (DOS) for conduct problems [Spatola et al, 2010;Bertoletti et al, 2014] or the externalizing scale of the CBCL encompassing the aggression and rule-breaking subscales [Burt and Klump, 2012;Robbers et al, 2012;Nikolas et al, 2013]. Meta-analyses have shown a distinction between aggression and rule-breaking, with the former primarily influenced by genetics and the latter by the shared environment [Burt, 2009[Burt, , 2013.…”
Section: Twin Studies Of Aggression As a Dimension Of Behaviormentioning
confidence: 99%
“…In Dutch studies, religious upbringing was found to decrease genetic variance of disinhibition [10], the experience of sexual assault to increase genetic variance of borderline personality features [11] and parental divorce to increase environmental variation in internalizing and externalizing problem behavior in children [12]. Earlier analyses of data from the Finnish twins used also in the present study have also illustrated effects of parental monitoring and home atmosphere on the heritability of adolescent substance use and externalizing behaviors associated with risk for early substance abuse [13].…”
Section: Introductionmentioning
confidence: 99%